Quality of life in adults with multiple sclerosis: a systematic review - Irene Gil-González; Agustín Martín-Rodríguez; Rupert Conrad; María Ángeles Pérez-San-Gregorio (BMJ Open)
Objective In recent years, quality of life (QoL) in multiple sclerosis (MS) has been gaining considerable importance in clinical research and practice. Against this backdrop, this systematic review aimed to provide a broad overview of clinical, sociodemographic and psychosocial risk and protective factors for QoL in adults with MS and analyse psychological interventions for improving QoL.Method The literature search was conducted in the Scopus, Web of Science and ProQuest electronic databases. Document type was limited to articles written in English, published from January 1, 2014, to January 31, 2019. Information from the selected articles was extracted using a coding sheet and then qualitatively synthesised.Results The search identified 4886 records. After duplicate removal and screening, 106 articles met the inclusion and exclusion criteria for qualitative synthesis and were assessed for study quality. Disability, fatigue, depression, cognitive impairment and unemployment were consistently identified as QoL risk factors, whereas higher self-esteem, self-efficacy, resilience and social support proved to be protective. The review analysed a wide spectrum of approaches for QoL psychological intervention, such as mindfulness, cognitive behavioural therapy, self-help groups and self-management. The majority of interventions were successful in improving various aspects of QoL.Conclusion Adequate biopsychosocial assessment is of vital importance to treat risk and promote protective factors to improve QoL in patients with MS in general care practice.